Динамика психофизиологических показателей у студентов в ходе короткого курса биоуправления по сердечному ритму - Луценко, Е.Л.; Спасенова, В.; Мартыненко, И.Г.; Мартыненко, В.В. (My University, 2015)
In this study it was tested efficiency of the short 4-session biofeedback course on heart rate. It was found that already on the 2nd session appear significant HRV enhancements. It was observed functional reserves optimization and psychological state improvement in general from the beginning to the end of the bfb-therapy course.
Keywords: психофизиология; вариабельность сердечного ритма; здоровье; качество жизни; самочувствие; активность; настроение